1976
DOI: 10.1104/pp.58.5.603
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Phosphoenolpyruvate Carboxykinase from Panicum maximum

Abstract: PEPCK has been characterized from several microorganisms and animals (1, 5-7, 9). However, only limited information is available on the characteristics of this enzyme in higher plants and most of this has been obtained using crude extracts (2, 10-14, 16, 18). In addition, the data on plant PEPCK are on either the exchange reaction or the ADP-dependent carboxylation reaction. Using either of these reactions to study PEPCK in relation to C4 photosynthesis is open to criticism since the proposed role of PEPCK is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

1979
1979
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 20 publications
1
7
0
1
Order By: Relevance
“…Utter & Kurahashi (171) first noted that PEP carboxykinase from chicken liver catalyzes the formation of pyruvate from oxaloacetate in the presence of IDP. A similar reaction has been demonstrated in yeast (21), and ADP-stimulated oxaloacetate decarboxylation has been reported with partially purified preparations of PEP carboxykinase from Panicum maximum (135) (32). However, the absence of ADP-stimulated oxaloacetate decarboxyla tion in preparations of PEP carboxykinase from Chloris gayana has been reported (62).…”
Section: Futile Cyclessupporting
confidence: 56%
“…Utter & Kurahashi (171) first noted that PEP carboxykinase from chicken liver catalyzes the formation of pyruvate from oxaloacetate in the presence of IDP. A similar reaction has been demonstrated in yeast (21), and ADP-stimulated oxaloacetate decarboxylation has been reported with partially purified preparations of PEP carboxykinase from Panicum maximum (135) (32). However, the absence of ADP-stimulated oxaloacetate decarboxyla tion in preparations of PEP carboxykinase from Chloris gayana has been reported (62).…”
Section: Futile Cyclessupporting
confidence: 56%
“…2A ). In contrast to the alkali pH 8 preference of PEPC ( Greenway et al , 1978 ), the activity of PEPCK is optimal at pH 7 and 80% lower at pH 8.0 ( Ray and Black, 1976 ; Pierre et al , 2004 ). To minimize, possibly preclude, PEPC activity, the extraction and measurement of PEPCK carboxylase activity was undertaken at pH 7.0 with Mg 2+ (required for PEPC activity) omitted and replaced with 2mM Mn 2+ , a PEPCK cofactor ( Fig.…”
Section: Resultsmentioning
confidence: 90%
“…270 kDa) suggesting that, in common with PEPCK from C 4 grasses (hexamer; Burnell 1986), yeast (tetramer; Tortora et al 1985) and Trypanosoma cruzi (dimer; Urbina 1987), the cucumber enzyme was a multimer. Whether or not these The activity of P E P C K was stable for several months when the purified preparation was stored at -20 ~ C. The presence of D T T was essential at all stages of the purification to prevent loss of activity (see also Ray and Black 1976;Burnell 1986). Kinetic studies using purified enzyme showed that it possessed similar kinetic properties to those of P E P C K s isolated from other plant tissues (Daley et al 1977;Leegood and ap Rees 1978;Burnell 1986).…”
Section: Resultsmentioning
confidence: 99%